Post-2001 Afghanistan : A critical analysis of the US WoT and state-building discourse(s) - Halimzai, Pamir; Eichler, Jan, 1952-; Rolenc, Jan Martin, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
How the US discourses on War on Terror and state-building in Afghanistan have taken shape, became dominant over the past 19 years and what are their consequences? Also, in what ways both discourses are representative of wider depoliticization of the society and paved the way for the illiberal, oppressive politics of confinement and necropolitics? These questions remain at the heart of this dissertation which, breaking away from rationalist and positivist convictions, does not frame and construct Afghanistan as a problem but instead, employs a poststructuralist theoretical toolkit coupled with Critical Discourse Analysis as a methodological framework and problematizes the discourses of three US presidents –George W. Bush, Barack Obama, and Donald Trump– vis-à-vis post-2001 Afghanistan. It argues that since Afghanistan is in a state of war for almost two decades, therefore the US discourse on War on Terror and the discourse of state-building imply each other, examining them independent of each other breaks down the holistic context and mars plausible explanations and conclusions. The dissertation offers an alternative history of Afghanistan which is deemed imperative to investigate the US War on Terror and state-building discourses and likewise reinterprets the Talibanization as a reverse state-building discourse, practice, and process. Afterwards, it revisits and offers a detailed analysis of the discourses of the three US presidents revealing a concatenation despite profound ideological differences among them. The US discourses thus remain stable yet keep expanding beyond Afghanistan. The study maintains that the US discourses could not tackle terrorism as a problem effectively and could not succeed in building robust security, democratic and economic apparatuses in Afghanistan. In its place, the US discourses paved the way for the emergence of phenomena that have resulted in a total subjugation of Afghanistan and its people.
I claim that the US discourses (and practices) resulted in the (evilized) depoliticization of the War on Terror in Afghanistan, making possible, what I call, the politics of confinement which is oppressive and illiberal. Whereas Bush laid the foundations for the politics of confinement which constituted spaces of confinement, Obama expanded those spaces and the domains of the politics of confinement. His drone war in Afghanistan, Pakistan, Iraq, Yemen, and other countries indicates the extension and growth of the spaces of confinement. The dissertation, drawing upon philosophical works of Foucault and Mbembe, establishes that the US War on Terror discourse operated in necropolitical ways in the post-2001 Afghanistan and equipped the Afghan ruling elite with the capacity and authority to exercise necropower. This theory-driven work contends that beside illiberalizing and oppressive consequences for Afghanistan, the US discourse on fighting terrorism has changed the ways of security practices and warfare because of the extensive use of semi/fully autonomous weapon systems. This transformation and reliance on artificial intelligence and machine learning has led to the rise of a new technology of power that this dissertation calls abiopower. At the end, through the help of the concept of abiopower, the dissertation attempts to construct a futurology of security practices, wars and bio/necropolitics.
Vedoucí práce: Jan Eichler
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní politické vztahy [obor disert. práce]; disertace; dissertations